The Effectiveness of Gamification in English Subject on Communicative Competence - Sari Safitri; Mai Zuniati; Rizky Hidayatullah (CV. Edutechnium Indonesia, 2025)
This study aims to determine the effectiveness of gamification in English learning among grade X students at SMA Negeri 01 Padang Ratu. Gamification, which involves the use of game elements in an educational context, is expected to increase student motivation and engagement. Through a quantitative approach, data were collected from 66 students using a pretest and posttest. The results showed that there was a significant influence between gamification in English subjects on the communication skills of grade X students of SMAN 01 Padang Ratu in the 2024/2025 Academic Year. Gamification not only increases students' confidence in speaking English, but also helps them understand the material better. This study concludes that gamification is an innovative method that is effective in improving the quality of English learning at the high school level.